Implementasi Sistem Keamanan Data Menggunakan Server Ubuntu Pada Jaringan Lokal di PT Coat Sedulur - Pramudhita Ferdiansyah; Zidan Fatur Rahman (Universitas Teknologi Mataram, 2024)
The data processing system in a company is very important, to make it easier for the company to manage and store data safely. However, managing this data requires an efficient and secure system to ensure there is no leak of company data. This research aims to implement a data processing system by dividing and limiting users and IP addresses to be able to access the server at PT Java Coat Sedulur. In addition to improving security aspects, the use of servers allows implementing stricter access controls, data encryption and sophisticated authentication systems. Centralized data management makes it easier to search, manage and share information, thereby increasing the company's operational efficiency. This research uses the Prepare Design Implement Operate and Optimize (PPDIOO) method as a network development framework that is centered on user needs. Ubuntu is used as the main server which functions to prevent viruses from entering the server. By setting the IP address, username and password in Samba, users can only access and manage files according to the specified jobdesk. The use of Samba for file sharing and folder sharing on the server shows that the client can connect well and successfully share files with the server. The results of implementing samba can create a secure and centralized data processing system, so that it can prevent data leaks